The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1109/access.2020.3020506
|View full text |Cite
|
Sign up to set email alerts
|

Mel-Weighted Single Frequency Filtering Spectrogram for Dialect Identification

Abstract: The second author would like to thank the Academy of Finland (Projects 312490 and 330139) for supporting his stay in Finland as a Postdoctoral researcher.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The experimental results demonstrate strong performance with an accuracy of 81.26%; these results were attained by using their techniques on a common dataset of 8 English accents. Similar works include [23,24,25,26].…”
Section: Related Workmentioning
confidence: 98%
“…The experimental results demonstrate strong performance with an accuracy of 81.26%; these results were attained by using their techniques on a common dataset of 8 English accents. Similar works include [23,24,25,26].…”
Section: Related Workmentioning
confidence: 98%
“…At the same time, North Sami dialects have been identified from audio by training several models, kNNs, SVMs, RFs, CRFs, and LSTM, based on extracted features (Kakouros et al, 2020). Kethireddy et al (2020) use Mel-weighted SFF spectrogram to detect spoken Arabic dialects. Mel spectograms are also used by Draghici et al (2020).…”
Section: Related Workmentioning
confidence: 99%
“…The SFF method was shown to provide better spectral features, such as harmonics, resonances (Chennupati et al, 2019;Pannala et al, 2016), and time-domain features, such as glottal closure instances and voice-onset time (VOT) (Kadiri and Yegnanarayana, 2017;Nellore et al, 2017). Inspired by the advantages of SFF, mel filter-bank energies derived from SFF (MFBE-SFF) were investigated with an SVM classifier in our previous studies (Kethireddy et al, 2020a), which showed promising results in identifying dialects compared to conventional STFT representations, such as the mel-spectrogram and MFCCs. In extension to the preliminary studies (Kethireddy et al, 2020a), this study proposes to derive four different feature representations: namely (1) SFF spectrogram (SPEC-SFF), (2) single frequency filtered cepstral coefficients (SFFCCs), (3) mel filter-bank energies derived from SFF spectrum (MFBE-SFF), and (4) mel-frequency cepstral coefficients derived from SFF spectrum (MFCC-SFF).…”
Section: Introductionmentioning
confidence: 99%